2014
DOI: 10.1111/resp.12326
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of ex vivo probe‐based confocal laser endomicroscopy and light microscopy in lung cancer diagnostics

Abstract: pCLE can identify lung carcinoma in ex vivo samples. Certain light microscopy features of lung carcinoma can be visualized with pCLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 14 publications
0
22
0
3
Order By: Relevance
“…5 Specifically, several reports have mentioned that pCLE can visualize the degeneration of elastic fibers (fragmentation, disorganization, clumping, and thickening) and shows dark hollow patterns with no elastic fiber structure as a result of destruction by tumor growth. 6,7 These findings correspond to interstitial changes that occur around cancer cells. Fuchs et al stained cellular nuclei using acriflavine and reported features of normal mucosa, inflammation/regeneration, and neoplastic lesions from characteristic structures of the cytoplasm and nucleus of airway epithelial cells and tissue architecture on pCLE analysis.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…5 Specifically, several reports have mentioned that pCLE can visualize the degeneration of elastic fibers (fragmentation, disorganization, clumping, and thickening) and shows dark hollow patterns with no elastic fiber structure as a result of destruction by tumor growth. 6,7 These findings correspond to interstitial changes that occur around cancer cells. Fuchs et al stained cellular nuclei using acriflavine and reported features of normal mucosa, inflammation/regeneration, and neoplastic lesions from characteristic structures of the cytoplasm and nucleus of airway epithelial cells and tissue architecture on pCLE analysis.…”
Section: Introductionmentioning
confidence: 64%
“…In the field of bronchoscopy, Thibervill et al reported pCLE imaging of the alveolus in 2009, and various reports of this imaging technique have subsequently been published . Specifically, several reports have mentioned that pCLE can visualize the degeneration of elastic fibers (fragmentation, disorganization, clumping, and thickening) and shows dark hollow patterns with no elastic fiber structure as a result of destruction by tumor growth . These findings correspond to interstitial changes that occur around cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Various processes disrupt this consistent elastin composition, including NSCLC. Recent work has shown that there are some specific changes seen on pCLE that correspond to specific diagnosis as seen on ex vivo tissue . The in vivo changes seen in lung cancer are the subjects of this project.…”
Section: Discussionmentioning
confidence: 99%
“…The pCLE images showed the differences among various subtypes of lung cancer according to the stromal and parenchymal component, allowing to identify lung carcinoma in ex-vivo samples (45). On the basis of these results, Wellikoff et al described the pCLE changes for in-vivo diagnoses of lung cancer.…”
Section: Clementioning
confidence: 99%